2012
DOI: 10.1128/iai.00024-12
|View full text |Cite
|
Sign up to set email alerts
|

Ingested Human Insulin Inhibits the Mosquito NF-κB-Dependent Immune Response to Plasmodium falciparum

Abstract: We showed previously that ingested human insulin activates the insulin/IGF-1 signaling pathway in Anopheles stephensi and increases the susceptibility of these mosquitoes to Plasmodium falciparum. In other organisms, insulin can alter immune responsiveness through regulation of NF-B transcription factors, critical elements for innate immunity that are also central to mosquito immunity. We show here that insulin signaling decreased expression of NF-B-regulated immune genes in mosquito cells stimulated with eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 52 publications
3
88
0
Order By: Relevance
“…Thus, the set point of ERK signaling in the gut may alter the permissivity to viral infection. In contrast, studies of Plasmodium falciparum in mosquitoes demonstrate that ingested human insulin increases the susceptibility of Anopheles stephensi by promoting replication of Plasmodium via the down-regulation of NF-κB signaling (51,52). Furthermore, ERK pathway activation by another mammalian blood product, TGF-β, in Anopheles mosquitoes has been found to down-regulate ROS production and also promote parasite growth (30).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the set point of ERK signaling in the gut may alter the permissivity to viral infection. In contrast, studies of Plasmodium falciparum in mosquitoes demonstrate that ingested human insulin increases the susceptibility of Anopheles stephensi by promoting replication of Plasmodium via the down-regulation of NF-κB signaling (51,52). Furthermore, ERK pathway activation by another mammalian blood product, TGF-β, in Anopheles mosquitoes has been found to down-regulate ROS production and also promote parasite growth (30).…”
Section: Discussionmentioning
confidence: 98%
“…Human insulin reduces lifespan and enhances parasite infection by suppressing A. stephensi immune processes (Kang et al, 2008;Surachetpong et al, 2009;Pakpour et al, 2012). In contrast, ingested human IGF1 can dose-dependently extend lifespan and enhance antiparasite immune responses in A. stephensi.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of midgut IIS can shorten mosquito lifespan and enhance susceptibility to P. falciparum infection in A. stephensi (Kang et al, 2008;Surachetpong et al, 2009). In particular, Pakpour et al (Pakpour et al, 2012) showed that insulin-induced susceptibility is due to the sustained activation of the phosphatidylinositol 3-kinase (PI3K)/Akt branch of the A. stephensi IIS, which in turn inhibits NF-κB-regulated immune gene expression. Furthermore, overexpression of Akt, a key IIS nexus protein, in the midgut of A. stephensi shortened lifespan and inhibited malaria parasite infection (Corby-Harris et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, human insulin and transforming growth factor beta in ingested blood can signal in the mosquito midgut to alter parasite infection. 16,17 Given that ABA has been detected in human blood in the nanomolar range, we hypothesized that mosquitoes could respond to ingested ABA. 7,18 Further, ABA regulation of granulocyte synthesis of RNOS-compounds that are essential to the mosquito immune response to Plasmodium infection-suggested that ABA could regulate analogous mosquito responses to developing parasites.…”
Section: Introductionmentioning
confidence: 99%